Competências Gerenciais Relevantes e em Desenvolvimento no Setor Hoteleiro de João Pessoa PB - Gondim, Cibelle Batista (2008)
The growing competitiveness in job market of the hotel sector has been requiring from its managers a constant search for new competencies that attend the demands of its specific functions. Considering the shortage of studies in this sector about which would be these competencies or how they have been developed, it was decided to do this research with the aim of filling this detected theoretical gap. Thus, this research has the aim of identifying the existing and developing competencies considered relevant to the Management of the hotel sector of João Pessoa PB. In order to do so it was developed a study of multiple cases of three middle sized companies of the hotel sector in the mentioned city. During all work, the usage of the Resources Competencies Diagram, proposed by Ruas (2001), was chosen as theoretical reference, being the concept of Competencies subdivided in Knowledges, Abilities and Attitudes. After the bibliographical review, a field research was developed with the application of questionnaires, which had the participation of 14 managers of these organizations. It was used the theme based content analysis technique, considering four variables: 1) Profile of the Vocational Training; 2) Courses and Trainings for the Managerial Development; 3) Management Competencies; and 4) Acquisition and Development of Management Competencies. Following a quanti-qualitative approach, the data were initially analyzed by company, then it was developed a general sinthesis of them what made possible to compare them with the information obtained in the theoretical review. Among the main results obtained we find the resources of competencies mentioned as relevant, according to the perception of the managers, and according to the theoretical review developed including a total of 15 knowledges; 11 abilities; and 30 attitudes. It is concluded that the competencies identified as relevant to the hotel sector are characterized as multifunctional , they are common to different managerial posts and analyzed sectors. Among the developing competencies, two were mentioned as results both of courses offered by the organizations and of courses searched by the managers themselves, which are: knowing how to meet the customs expectations and knowing how to cultivate interpersonal relationships . Besides, the daily practice of the profession was considered the most important way of learning for the development of competencies, according to the perception of participants of the research.